The Effect of E-Service Quality on E-Satisfaction through E-Trust as a Mediating Variable in ShopeePay Users in Cirebon City - Firman Jonathan Sitanggang,; Nurrudin,; Soesanty Maulany, (Jurnal Manajemen, 2025)
The number of Indonesians using financial technology, or fintech, is growing annually. ShopeePay is one of the most popular digital wallets. How satisfied consumers are with internet services is largely determined by the calibre of electronic services. Furthermore, the relationship between e-service quality and e-satisfaction may be strengthened by the mediating function of customer electronic confidence in digital platforms. This study aims to investigate the relationship between e-service quality and e-satisfaction, utilising e-trust as a mediating variable for ShopeePay users in Cirebon City. Regression-based data analysis tools and mediation tests are part of the quantitative research methodology. By the application of non-probability purposive sampling. Because the population in this investigation is unclear, the researchers used Lemeshow's rumus to determine the number of samples. 400 respondents in all were used in this investigation. The quality of e-services thus has a positive and considerable impact on e-satisfaction. E-trust is positively and significantly impacted by the quality of e-services. E-satisfaction is positively and significantly impacted by e-trust. Furthermore, e-service quality has a considerable and positive influence on e-satisfaction, which is gauged by e-trust.